Determinants of Clean and Healthy Household Living Behavior in the Margamulya Health Center Area, Bekasi City - Pansilia Pansilia; Rifa’at Hanifa Muslimah (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Housewives have a very big role in providing examples, educational examples in a household than fathers. Mothers are also more dominating in all things and also in maintaining household cleanliness, including in providing household health education, such as instilling clean and healthy living behaviors (PHBS). Objective: To assess the Determinants of PHBS households in the Margamulya Health Center area. Methods: This study used a quantitative approach with a cross sectional design. The population is 5,653 residents, with a sample size of 98 respondents taken using accidental sampling. Data collection uses an instrument in the form of a self-filling questionnaire. Data analysis is univariate, bivariate and multivariate. Results and Discussion: The analysis showed that there was a relationship between knowledge, attitudes, household income, health counseling, household support and community leader support with household PHBS in the Margamulya Health Center area, Bekasi City. The dominant variable related to PHBS behavior is attitude. Conclusion: Attitude is the dominant variable related to PHBS